Biological activities associated with the volatile compound 2, 5-bis(1-methylethyl)-pyrazine. Issue 3 (29th January 2019) - Janssens, Thierry K S; Tyc, Olaf; Besselink, Harrie; de Boer, Wietse; Garbeva, Paolina
ABSTRACT: Pyrazines are 1, 4-diazabenzene-based volatile organic compounds and known for their broad-spectrum antimicrobial activity. In the present study, we assessed the antimicrobial activity of 2, 5-bis(1-methylethyl)-pyrazine, produced by Paenibacillus sp. AD87 during co-culture with Burkholderia sp. AD24. In addition, we were using transcriptional reporter assays in E. coli and mammalian cells to decipher the possible mode of action. Bacterial and mammalian luciferase reporter strains were deployed to elucidate antimicrobial and toxicological effects of 2, 5-bis(1-methylethyl)-pyrazine. At high levels of exposure, 2, 5-bis(1-methylethyl)-pyrazine exerted strong DNA damage response. At lower concentrations, cell-wall damage response was observed. The activity was corroborated by a general toxicity reporter assay in E. coli Δ ampD, defective in peptidoglycan turnover. The maximum E. coli cell-wall stress activity was measured at a concentration close to the onset of the mammalian cytotoxicity, while other adverse outcome pathways, such as the activation of aryl hydrocarbon and estrogenic receptor, the p53 tumour suppressor and the oxidative stress-related Nrf2 transcription factor, were induced at elevated concentrations compared to the response of mammalian cells. Because of its broad-spectrum antimicrobial activity at lower concentrations and the relatively low mammalian toxicity, 2, 5-bis(1-methylethyl)-pyrazine is a potential bio-based fumigant with possible applications in food industry, agriculture or logistics. Abstract : In the current study, we explore the toxicity, antmicrobial activity and the mode of action exhibited by 2, 5-bis (1-methylethyl)-pyrazine using bacterial and mammalian cell-based bioreporters.